The Effect of Guided Discovery Models on Students' Understanding of Concepts on Straight Motion Material - Nur Aida; Arusman; Siti Mauliyana; Muhammad Daud (Winaya Inspirasi Nusantara Foundation, 2020)
The selection of the right model will facilitate the process of forming knowledge in students. One model that can be used in the process is the guided discovery model, the purpose of this study is to find several points as follows: the influence of the Guided Discovery model on understanding students 'concepts in straight motion material, the students' responses after their application, the teacher's activities when applying the guided model discovery on straight motion material. The results of the study can be concluded as: 1. Ha is accepted if t-count is greater than t-table. From the above calculation, it is clear that t-count> t-table (11.30> 1,725). This indicates that Ha was accepted and Ho was rejected. Therefore, the influence of the guided discovery model can affect the understanding of the concept of students in SMA N 1 Baitussalam Aceh Besar. 2. The response of students looks very good. 3. That the results of observations of teacher activity in the learning process by using the guided discovery model of understanding the concepts of students get a very active value that is 87.45%. While observations of the activities of educators in the learning process by using the guided discovery model of understanding the concepts of students get a very active value of 83.87%.